Entrepreneurship and new venture management - Onmonya, Lucky O.; Institute of Development Finance and Project Management (Abuja : Issues &bCompany Institute of Development Finance and Project Management, 2011)
Provides an understanding of the need for small businesses in the industrialization and transformation of the Nigerian economy.
Includes bibliographical references and index.
oif 09/09/14
Loan
Keywords: Entrepreneurship -- Nigeria; Small business enterprises -- Nigeria; Entrepreneurship; Small business enterprises